Effectiveness of HEPA Filters at Removing Infectious SARS-CoV-2 from the Air - Ueki, Hiroshi; Ujie, Michiko; Komori, Yosuke; Kato, Tatsuo; Imai, Masaki; Kawaoka, Yoshihiro (mSphere, 2022)
Air filtration simulation experiments quantitatively showed that an air cleaner equipped with a HEPA filter can continuously remove SARS-CoV-2 from the air. The capture ratios for SARS-CoV-2 in the air when the air cleaner was equipped with an antiviral-agent-coated HEPA filter were comparable to those with the conventional HEPA filter, and there was little effect on SARS-CoV-2 in the air that passed through the antiviral-reagent-coated HEPA filter. Coronavirus disease 2019 (COVID-19) spreads by airborne transmission; therefore, the development and functional evaluation of air-cleaning technologies are essential for infection control. Air filtration using high-efficiency particulate air (HEPA) filters may be effective; however, no quantitative assessment of the effectiveness of these filters in the removal of infectious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) from the air has been reported. To evaluate the removal effect of HEPA filtration on airborne SARS-CoV-2, here, we disseminated infectious SARS-CoV-2 aerosols in a test chamber in a biosafety level 3 facility and filtered the air with a HEPA-filtered air cleaner in the chamber. The air cleaner with the HEPA filter continuously removed the infectious SARS-CoV-2 from the air in a running-time-dependent manner, and the virus capture ratios were 85.38%, 96.03%, and >99.97% at 1, 2, and 7.1 ventilation volumes, respectively. The air-cleaning performance of a HEPA filter coated with an antiviral agent consisting mainly of a monovalent copper compound was also evaluated, and the capture ratio was found to be comparable to that of the conventional HEPA filter. This study provides insights into the proper use and performance of HEPA-filtered air cleaners to prevent the spread of COVID-19. IMPORTANCE Air filtration simulation experiments quantitatively showed that an air cleaner equipped with a HEPA filter can continuously remove SARS-CoV-2 from the air. The capture ratios for SARS-CoV-2 in the air when the air cleaner was equipped with an antiviral-agent-coated HEPA filter were comparable to those with the conventional HEPA filter, and there was little effect on SARS-CoV-2 in the air that passed through the antiviral-reagent-coated HEPA filter.